Sexualities, Gender and Violence. A view from the Iberian Peninsula - Alvarez, Bruna (Quaderns de l’Institut Català d’Antropologia, 2021)
Sexualities, Gender and Violence. A view from the Iberian Peninsula. Begonya Enguix Grau i Cristina Pereira Vieira (Eds.) (2020). New York: Nova Science Publishers. 262 p. ISBN: 978-1-53618-173-9